PENINGKATAN PEMAHAMAN KONSEP NILAI TEMPAT BILANGAN MELALUI MEDIA GELAS WARNA PADA SISWA KELAS I SDN PURWANTORO 2 MALANG - Farhatul Hakiki; Dyah Worowirastri Ekowati; Wiwik Susintowati (Universitas Muria Kudus, 2019)
This study aims to determine the increase in understanding of the concept of place number values in class 1B students by using color glass media at SDN Purwantoro 2 Malang. This study uses qualitative research and the type of research is classroom action research. The data sources are class 1 of SDN Purwantoro 2 Malang, totaling 25 students and class 1B teachers. The data obtained in the form of understanding concept of place number value seen from the value of student learning outcomes. Data collection techniques used were observation, interviews, tests, and documentation. Time of study January to February 2019. This study was conducted in 2 cycles and each cycle had 2 meetings. Each cycle has 4 stages, namely preparation, implementation, observation, and reflection. The application of color glass media increases the understanding of the concept of place number values in class 1B students at SDN Purwantoro 2 Malang. It is shown that understanding the concept of place number values seen from student learning outcomes in the pre-cycle average value of students at 63.2 increased to 66.6 in the first cycle and 81.6 in the second cycle with the percentage of completeness from 36% in the pre-cycle to 56% in the cycle I and 80% in cycle II.